Supplementary Materials: Drought or Wet Assessment of Daily Rainfall Pattern of the Budhi Gandaki River Basin, Nepal: Standardized Precipitation Index Approach Using Probabilistic Model - Shrestha, Rajendra Man (Nepalese Journal of Statistics, 2020)
Supplementary material for the article on pages 57-72 https://doi.org/10.3126/njs.v4i0.33497